Influence of tablets on motivation towards English learning - Muñoz Millet, Ornela María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this research is to analyse the use of tablets as a motivating resource for learning English. Regarding the method, sixteen 11-year-old students from the sixth grade of primary education from a preferred educational action school in the Region of Murcia participated in this study. A quasi-experimental study with pre-test and post-test measures was designed. Statistical analyses showed a significant increase in the children’s extrinsic motivation. As conclusions, it is determined that the sociocultural context of the participants could have influenced the results and extend this research to a larger sample of participants.